Connection Charges and Electricity Access in Sub-Saharan Africa - Golumbeanu, Raluca; Barnes, Douglas (World Bank, Washington, DC, 2013)
Sub-Saharan Africa trails other regions in providing access to electricity for poor urban and rural residents. This poor performance can be linked to various factors, including political interference in utility policy, higher investment costs and lower profitability of extending service to rural areas. But a major obstacle to wider access is the high charges consumers must pay to connect to the electricity network. The connection charges in Sub-Saharan Africa are among the highest in the world, which has resulted in low rates of electrification in many countries. This paper reviews ways to improve electrification rates by addressing the issue of high connection charges. Essential to the success of such efforts is concurrent political commitment to identify, examine, and implement various low-cost electrification approaches and financing solutions as part of a broad plan to improve access. Electricity companies can lower their connection-related costs, and thus consumer charges, by using a variety of low-cost technologies and materials in distribution networks and household connections; making bulk purchases of materials; and adjusting technical standards to reflect the lower loads of households that use a minimum amount of electricity. Strategies for lowering connection charges may also include spreading charges over a reasonable period, rolling them into monthly service payments, subsidizing connections, or amortizing them through loans. Lowering connection charges is not the only step, but it is an essential part of any strategy for addressing the electricity access gap between rich and poor households in Sub-Saharan Africa, a gap that denies millions of poor Africans the benefits of electricity.